Influence of Talent Management Practices on Performance of State Corporations in Kenya - Wanjugu, Nderi Caroline; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
The greatest asset for any Country in general and Organization in particular is its humancapital. In the recent past the performance of State Corporations is becoming a challenge inpublic service resulting to loss of government funds, this is great loss in a country. Talentmanagement is therefore crucial and indispensable for any organization’s managementpractice. Talent Management Practices has been recognized by many authors as animportant Human resource management practice. Talent management practices areimportant in the ever changing global environment and in the in state corporations, are noexception. The objective of this study was to determine the influence of talent managementpractices on State Corporations’ performance in Kenya. The specific objectives were; toevaluate the influence of performance Management on firm performance, to establish theinfluence of training and development on firm performance, to establish the influence ofreward systems on firm performance and to assess the influence of employee empowermenton firm performance of State Corporations in Kenya. The scope of the study was the StateCorporations in Kenya. The target population of the study was the Human Resourcesmanagers/equivalent in all the 147 state Corporations in Kenya. The study used censusapproach to reach all the Human Resources managers/equivalent in all the 147 stateCorporations in Kenya. A questionnaire was used as the main data collection tool to collectprimary data. Secondary data on state corporations’ performance were obtained fromdocumentaries and published reports available. Piloting of the instruments was done beforethe actual data collection to test on the reliability. Authorization letter for data collectionwas obtained from Jomo Kenyatta University. The primary data collected was analysedthrough the use of descriptive statistics where the SPSS Ver. 21.0 was used as the aid tool.Frequency tables, percentages, mean and standard deviation, pie charts, charts and graphswere used to present the analysed data. The study found out that reward management leadsto improved performance in the state corporations in Kenya by enhancing targetachievement, improving customer satisfaction and improving corporation ranking, trainingand development leads to improved performance in the state corporations in Kenya byenhancing target achievement, improving customer satisfaction, and improving corporationranking,; performance management in the state corporations in Kenya leads to improvedperformance by enhancing target achievement, improving customer satisfaction, andimproving corporation ranking, employee empowerment in state corporations in Kenya leadsto improved performance by enhancing target achievement, improving customer satisfactionand improving corporation ranking. The study concluded that talent management practicesin state corporations in Kenya improve performance. the study recommended that statecorporations introduce a more competent strategy for rewarding their employees, trainingand development should be a practice employed on all employees of the state corporationsnot just those on top, and employee empowerment should not only be done to the top andmiddle level employees but to those at the bottom level management as well for they oftenfeel left out